Putting lives back in to the waters: Good management practices in sportfishing - Souza, Robson Oliveira de (Brasil, 2024)
The main mortality factors of fish that are caught and then returned to the water are stress, injuries to fundamental organs and the time taken when handling the fish while it is out of the water. Some factors, such as stress, cannot be completely avoided. However, small changes in fishing procedures, with the adoption of good handling practices are key points for reducing the mortality rate of sport-caught fish. These good practices apply to all the stages of the activity, from the proper choice of fishing gear to the procedures for releasing fish into the water. Next, we will discuss these steps, in order to present the practices that should be adopted by sportfishers who visit the Amazon.